2021
DOI: 10.1088/1757-899x/1137/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional effects on the performance of multi-level overtopping wave energy converter

Abstract: The performance of a multi-level overtopping wave energy converter has been numerically investigated in a three-dimensional wave tank. The device has three extra slots and is positioned on a breakwater. The span length of the breakwater is the main parameter associated with the three-dimensional effects on the hydraulic efficiency of the wave energy device. It has been shown that the device with a finite span yields a lower captured crest energy due to waves falling-down the edges during the run-up process. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Some experimental studies about the Overtopping Device Wave Energy Converter (OTD-WEC) are found, such as: [4][5][6][7][8][9][10]. There are also studies into the numerical framework: [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Concerning the employment of Constructal Design and numerical simulation in the OTD-WEC, the number of works has increased, highlighting: [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Some experimental studies about the Overtopping Device Wave Energy Converter (OTD-WEC) are found, such as: [4][5][6][7][8][9][10]. There are also studies into the numerical framework: [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Concerning the employment of Constructal Design and numerical simulation in the OTD-WEC, the number of works has increased, highlighting: [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%